Performance of anammox biofilm reactor under tropical temperature. Issue 1 (January 2021) - Zulkarnaini, Z; Primasari, B; Saputra, D J
Abstract: Application of anaerobic ammonium oxidation (anammox) process for mainstream wastewater in the lower temperature is a current challenge where most of the anammox reactors planted in the sub-tropical country. The purpose of this study was to analyze the performance of nitrogen removal using anammox process at room temperature in a tropical country. The experiment was carried out using 300 mL an up-flow anaerobic sludge blanket (UASB) reactor in treating low ammonia concentration artificial wastewater at tropical temperature without any adjustment. The reactor filled with 50% in volume spiral-sheet plastic (polyethylene terephthalate) as the carrier. Anammox bacteria Candidatus Brocadia sinica as seeding acclimatized in room temperature for three months before the experiment. The reactor fed with 70 mg-N/L for both ammonium and nitrite with variations in hydraulic retention time (HRT) 24 hours and 12 hours. The maximum nitrogen removal rate (NRR) achieved 0.12 kg-N/(m 3 ·d) at nitrogen loading rate (NLR) 0.14 kg-N/(m 3 ·d) and NRR 0.25 kg-N/(m 3 ·d) at NLR 0.28 kg-N/(m 3 ·d). The anammox process was stable at room temperatures (15-28°C) in a tropical country for nitrogen removal and anammox bacteria grown on plastic media.